2010
DOI: 10.1111/j.1365-2036.2010.04373.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: steroid withdrawal in anti‐TNF‐treated patients with inflammatory bowel disease

Abstract: SUMMARY BackgroundThe increasing awareness of increased risk for opportunistic infections when combining several immunosuppressant drugs led to new treatment goals for inflammatory bowel disease including limited use of steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…5 0 -ASA blocks production of prostaglandins and leukotrienes and is used to induce remission in active UC and is also useful in maintaining remission [14]. Systemic corticosteroids are useful for acute flare-ups of most forms of IBD [15]. Azathioprine is used as an immunomodulatory agent in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…5 0 -ASA blocks production of prostaglandins and leukotrienes and is used to induce remission in active UC and is also useful in maintaining remission [14]. Systemic corticosteroids are useful for acute flare-ups of most forms of IBD [15]. Azathioprine is used as an immunomodulatory agent in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used in a small number of patients as a long term maintenance treatment in patients who are refractory or intolerant to other treatments and in whom more extensive surgery is not a viable option. IFX treatment allows catch up growth and reduces steroid use in paediatric patients with CD 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review evaluated the steroid-sparing effect of anti-TNF agents in patients with IBD [39]. Authors reported that 30% of all adult patients treated with steroids and IFX at baseline were able to remain steroid free without further complications.…”
Section: Efficacy Beyond Clinical Remission: Hospitalization Surgerymentioning
confidence: 99%